Etiese perspektiewe vir die bantering van konflik in die mediese wetenskap - Lategan, L. O. K. (Hervormde teologiese studies, 1993)
Ethical perspectives in dealing with conflict in the medical sciences Medical practice is daily confronted with the problem how to deal with ethical conflict. This matter becomes even more difficult when one deals with boarder-situations such as abortion and euthanasia. Here a choice is required between life and death. But it is important to bear in mind that approaching ethical situations requires knowledge of powers such as ideology, technique, etc and paradigms such as Christian anthropology which influence our decisions. Therefore, it seems that ethical models such as situation ethics and casuistry are insufficient to deal with the problem of conflict. In this paper a ethical model is presented to deal with conflict in medical ethics. This model - contextual normative ethics - tries to compromise an ethical dilemma.